A Simultaneous Extraction/Derivatization Strategy for Quantitation of Vitamin D in Dried Blood Spots Using LC–MS/MS: Application to Biomarker Study in Subjects Tested for SARS-CoV-2 - Chhonker, Yashpal S.; Ahmed, Nusrat; Johnston, Christine M.; Barnabas, Ruanne V.; Murry, Daryl J. (International journal of molecular sciences, 2023)
Vitamin D plays a critical role in bone development and maintenance, and in other physiological functions. The quantitation of endogenous levels of individual vitamin D and its metabolites is crucial for assessing several disease state conditions. With cases of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) leading to the coronavirus disease 2019 (COVID-19) pandemic, there are several studies that have associated lower levels of serum vitamin D with severity of infection in COVID-19 patients. In this context, we have developed and validated a robust LC–MS/MS method for simultaneous quantitation of vitamin D and its metabolites in human dried blood spot (DBS) obtained from participants tested for COVID-19. The chromatographic separation for vitamin D and metabolites was performed using an ACE Excel C18 PFP column protected with a C18 guard column (Phenomenex, Torrance, CA, USA). The mobile phase consisted of formic acid in water (0.1% v/v) as mobile phase A and formic acid in methanol (0.1% v/v) as mobile phase B, operated at a flow rate of 0.5 mL/min. Analysis was performed utilizing the LC–MS/MS technique. The method was sensitive with a limit of quantification of 0.78 ng/mL for all analytes, and had a large dynamic range (200 ng/mL) with a total run time of 11 min. The inter- and intraday accuracy and precision values met the acceptance criteria per the US Food and Drug Administration guidelines. Blood concentrations of 25(OH)D3, vitamin D3, 25(OH)D2, and vitamin D2 over a range of 2–195.6, 0.5–121.5, 0.6–54.9, and 0.5–23.9 ng/mL, respectively, were quantified in 909 DBS samples. In summary, our developed LC−MS/MS method may be used for quantification of vitamin D and its metabolites in DBS, and may be applied to investigations of the emerging role of these compounds in various physiological processes.